Regulatory T Cells and Acute Lung Injury: Cytokines, Uncontrolled Inflammation, and Therapeutic Implications - Lin, Shihui; Wu, Hua; Wang, Chuanjiang; Xiao, Zhibo; Xu, Fang (Frontiers in Immunology, 2018)
Acute respiratory distress syndrome (ARDS)/acute lung injury (ALI) was described in 1967. The uncontrolled inflammation is a central issue of the syndrome. The regulatory T (Treg) cells, formerly known as suppressor T cells, are a subpopulation of T cells. Treg cells indirectly limits immune inflammation-inflicted tissue damage by employing multiple mechanisms and creating the appropriate immune environment for successful tissue repair. And it plays a central role in the resolution of ALI. Accordingly, for this review, we will focus on Treg cell populations that are critical for inflammatory immunity of ALI, and the effect of interaction between Treg cells and cytokines on ALI.